The effect of e-commerce service quality on customer satisfaction, trust and loyalty - Fajar Pasaribu; Warsani Purnama Sari; Tapi Rondang Ni Bulan; Widia Astuty (International Journal of Data and Network Science, 2022)
This study aims to explain the effect of service quality on satisfaction, service quality on trust, service quality on loyalty, satisfaction on loyalty and trust on loyalty. The population in this study are all consumers who have made transactions at an Indonesian marketplace, Shopee.co.id. The number of respondents used as a sample is 300 respondents. The results showed a significant influence between variables in the four interaction effects, namely service quality on satisfaction, service quality on trust, satisfaction with loyalty, and trust in loyalty. Meanwhile the insignificant effect was service quality on loyalty, the results of the total effect calculation also showed that Trust is a mediating variable between service quality and loyalty. marketing stimuli that can be carried out include maintaining cash on delivery services to increase customer trust, optimizing customer satisfaction through service improvement, providing more organized information so that consumers are easier and more comfortable in transacting, providing a 'tracking order' stage for customers, so that customers can monitor the progress of product orders. For further research, it is hoped that it can develop more variables under study and make comparisons of other e-commerce both in Indonesia and internationally.